Don de lenguas - Ribas, Rosa; Hofmann, Sabine, 1964- (Nuevos tiempos (Madrid, Spain), 2013)
Ana, a young rookie journalist is assigned to cover the murder case of Mariona, a famous bourgeoisie widow. When she discovers a series of mysterious letters involving influential people in high society Barcelona, Ana reaches out for help from her cousin Beatriz, an expert in linguistics, in order to solve the case.